Developing Test Specifications For Measuring Listening Performance Of Tertiary Students - Ahmad, Irma (2023)
Reports from the Malaysian Examination Council have shown a worrying trend in the Malaysian University English Test (MUET) listening component since 2010, where nearly half of the candidates were reported as ‘limited’ and ‘very limited’ users. This indicates a lack of listening skills among the candidates and thus, proof that there is a gap in English language listening proficiency between pre-university and tertiary education. A preliminary study was conducted in the study and participants were reported as not being not aware of their listening abilities and agreed to have a listening comprehension test to measure their listening proficiency skills. However, there are limited guidelines for designing and developing effective listening comprehension tests, especially for the tertiary students. Thus, this study was aimed to develop a listening test specification that can be used to measure tertiary students’ listening performance. There were two objectives of the study: (1) to develop a listening comprehension test specification to measure students’ listening performance, and (2) to validate the test specification by using elements from Weir’s socio-cognitive framework. The study employed a mixed method. Questionnaires, focus-group interviews, and content validation were used to collect the data. The quantitative data collected were analysed by using Statistical Packages for Social Sciences (SPSS) and thematic analysis was used to analyse the data collected from focus-group interview.